Suitability of Mangrove Ecotourism Areas in Teluk Barukang Talisayan District Berau Regency - Wempi Agung Massolo; Muhammad Yasser; Nurfadilah Nurfadilah; Omega Raya Simarangkir (Fakultas Perikanan dan Kelautan, Universitas Riau, 2022)
Dumaring village village has a tourist area, namely Barukang Bay, especially in mangrove plants which have been around for a long time but have not received sustainable management until now from the government and local communities. This study aims to determine the condition of mangrove and feasibility research sites for ecotourism activities in Teluk Barukang Dumaring Subdistrict in Talisayan. This research was conducted in January 2021, in Teluk Barukang Dumaring Subdistrict in Talisayan. This research is based on three stages. The first stage of the preparation, and then conducted a survey observations, and determination of the samplin point, and then do the data collection, and the last stage analysis of the data. Based on the results of research in the fieled, discovered three species of mangrove, incluiding: sonneratia alba, Avicennia alba, Rhizopora apiculata. And in the terms the value of mangrove density in general, the value obtained is still relatively low. Reviewed using a tourism suitablility index, showing that mangrove areas in Teluk Barukang Dumaring Village still in the conditionally appropriate category (S2).